Tinjauan Yuridis Tanggung Jawab Hukum Terhadap Perjanjian Penyelenggaraan Pameran Antara Pt. Assalam Hypermarket Sebagai Penyelenggara Dengan Peserta Pameran Buku Islam - Setiawan, Suseno Candra, Nuswardhani, S.H., S.U, Septarina Budiwati, S.H., M.H (2016)
The purpose of this study is to analyze the process and form of agreement which is the basis of the legal relationship between the organizers and participants of Islamic Book Fair in Assalam Hypermarket, the rights and obligations of the organizers and exhibitors, as well as analyze the responsibility of the law in case of default of the parties in the implementation of Islamic Book Fair. This research includes normative legal research. Research conducted at the Assalam Hypermarket Pabelan Kartasura. Source data using secondary data. Data were analyzed using qualitative analysis. The results showed that: First, the Agreement between the Giant Hypermarket Assalam Promosindo is a lease agreement based on the agreement of both parties. Giant Promosindo as the tenant is entitled to use the facilities in place and Assalam Hypermarket for Islamic Book Fair in organizing the event. Furthermore, the agreement between Giant Promosindo with exhibitors form of a cooperation agreement with the basic organization of exhibitions lease, where the exhibitors renting exhibition stand to exhibition organizers; Second, the right Assalam Hypermarket is receive payment for the cost of all usage place and obligation is to provide the venue with amenities. Giant rights Promosindo is to use the venue with trimmings and get right of payment exhibitors. Giant obligation Promosindo is: pay the entire cost of the venue and their facilities to Assalam Hypermarket Rights exhibitors is getting the exhibition stand and promotional facilities, while liabilities exhibitors are paying the registration fee as exhibitors; Third. Default is unprecedented in the Islamic book exhibition is a delay in lease payments from the organizers to Assalam Hypermarket. An unlawful act that occurred in the placement of the exhibition is the presence of a fault related to a problem concerning the payment of rent is not paid immediately, the organizers do not carry out promotions, and so on. However, these problems can be solved either by way of the family without having to take legal action. Keywords: process and shape the exhibition agreement, the rights and obligations of the participants and organizers of the exhibition, default in exhibition ¬